Mitigating Noise and Interference in Audio Signal during Virtual Meetings Using Audio Porting in Digital Signal Processing (APS) - Aburuotu, E.C; Ledisi Kabari (PhD) (International Journal on Human-Computing Studies, 2021)
Virtual Meetings has become part of our everyday activities and they are now part of our life because of the new-normal brought about by Covid-19 in the year 2020. Virtual meetings are held either on audio/video, video or audio modes and each of the modes are transmitted through a digital signal processing which produces noise and interference. This paper will demonstrate and apply signal processing methods through audio cable for noise reduction. This is necessary because virtual meetings can be a source of stress if the voice output coming from the audio systems is not clear and noiseless. It will identify various types of noise experienced during virtual meetings and propose a method of physical hardware integration to mitigate noise during a virtual presence. The study will also demonstrate ways in which local meeting hosts and participants can handle some hardware connections outside the methodology of this study and have a noiseless virtual centre. This paper will benefit users of various virtual applications, virtual application developers, schools, government organizations and others